2016
DOI: 10.1007/s11270-016-3147-x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Water Percolating Through Soil Fertilized with Biodegradable Waste Materials

Abstract: The influence of manure and composts on the leaching of heavy metals from soil was evaluated in a model lysimeter experiment under controlled conditions. Soil samples were collected from experimental fields, from 0- to 90-cm layers retaining the layout of the soil profile layers, after the second crop rotation cycle with the following plant species: potatoes, spring barley, winter rapeseed, and winter wheat. During the field experiment, 20 t DM/ha of manure, municipal sewage sludge composted with straw (SSCS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…Still, measured concentrations were below the limit of 50 µg L −1 of total Cr, which is a recommended value for fresh waters (World Health Organization, 2006). The values measured in both seasons were comparable to those found in a similar field experiment reported by Wierzbowska et al where values were also below 50 µg L −1 (Wierzbowska et al, 2016). In the pH range measured for both growing seasons, Cr(III) is expected to be the predominant form of Cr present in the soil solution (Bradl, 2004;Choppala et al, 2018).…”
Section: Influence Of Biogas Digestates Fertilization On Trace Metalssupporting
confidence: 89%
“…Still, measured concentrations were below the limit of 50 µg L −1 of total Cr, which is a recommended value for fresh waters (World Health Organization, 2006). The values measured in both seasons were comparable to those found in a similar field experiment reported by Wierzbowska et al where values were also below 50 µg L −1 (Wierzbowska et al, 2016). In the pH range measured for both growing seasons, Cr(III) is expected to be the predominant form of Cr present in the soil solution (Bradl, 2004;Choppala et al, 2018).…”
Section: Influence Of Biogas Digestates Fertilization On Trace Metalssupporting
confidence: 89%
“…For dissolved Pb, the urban waste treatments did not exhibit significantly higher concentrations than the unfertilized control (U). These results are in contradiction with the results obtained by Wierzbowska et al (2016), who found that Cr and Pb were elevated in water leaching from soil fertilized with urban waste fertilizers compared with a control. Furthermore, these researchers (Wierzbowska et al, 2016) generally found much higher concentrations of both Cr (36.7–96.5 μg L −1 ) and Pb (113.8–187.7 μg L −1 ) than were found in the present study.…”
Section: Resultscontrasting
confidence: 99%
“…Much less emphasis has been put on the agricultural use of organic waste composts (Basta et al, 2005), although recently the leaching of metals from agricultural soil treated with different waste composts has been investigated in a study using lysimeters installed in the field (Cambier et al, 2014). Wierzbowska et al (2016) studied the leaching of heavy metals from soils that had been fertilized with either agricultural fertilizers or a range of biological waste materials using model lysimeters.…”
Section: Topsoil Content Of Organic C Cu and Zn For The Investigatementioning
confidence: 99%
“…However, due to the positive balance of these elements in soil, long-term use of sewage sludge may be problematic, especially when soil acidity increases, in the consequence of which the mobility of elements and their leachability rise (Sevel et al 2014 ). In a study conducted by Wierzbowska et al ( 2016 ), soil fertilization with organic waste did not pollute leachate water with Mn and Zn, while content of other metals rose to a level typical of unsatisfactory or even poor quality water. The content of Cu and Ni in leachate water depended on the quantities of other metals imported to soil with organic materials, for example, content of Cu and Ni decreased as the content of C-org.…”
Section: Resultsmentioning
confidence: 91%